2011
DOI: 10.1186/2191-219x-1-31
|View full text |Cite
|
Sign up to set email alerts
|

Inert coupling of IRDye800CW to monoclonal antibodies for clinical optical imaging of tumor targets

Abstract: BackgroundPhotoimmunodetection, in which monoclonal antibodies [mAbs] are labeled with fluorescent dyes, might have clinical potential for early detection and characterization of cancer. For this purpose, the dye should be coupled in an inert way to mAb. In this study, different equivalents of IRDye800CW, a near-infrared fluorescent dye, were coupled to 89Zr-labeled cetuximab and bevacizumab, and conjugates were evaluated in biodistribution studies. Radiolabeled mAbs were used to allow accurate quantification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 35 publications
7
77
0
2
Order By: Relevance
“…Enhanced hepatic uptake of IRDye800CW-conjugated antibodies has been reported in previous studies. Cohen et al (23) reported enhanced liver uptake of the dual-labeled antibodies 89 Zr-cetuximab-IRDye800CW and 89 Zr-bevacizumab-IRDye800CW in vivo, which was attributed to the lipophilicity and charge of the antibody conjugate. In this study, a substitution ratio of less than 2 was found to be optimal to prevent enhanced blood clearance and hepatic liver uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced hepatic uptake of IRDye800CW-conjugated antibodies has been reported in previous studies. Cohen et al (23) reported enhanced liver uptake of the dual-labeled antibodies 89 Zr-cetuximab-IRDye800CW and 89 Zr-bevacizumab-IRDye800CW in vivo, which was attributed to the lipophilicity and charge of the antibody conjugate. In this study, a substitution ratio of less than 2 was found to be optimal to prevent enhanced blood clearance and hepatic liver uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This has been a major barrier to the adoption of many otherwise excellent fluorescent labels. Controlling the labeling sites and limiting the stoichiometry (19,20) should minimize the risk of immunogenicity and the problems of batch-to-batch heterogeneity, helping the validation of fluorescent labels in clinical and other critical settings (4). With optical and radioactive labels alike, incorporating more labels per protein [up to 10 of each in Sampath et al (21)] gives rise to a temptingly "brighter" protein with higher specific activity or fluorescent yield, but this is a siren call risking compromised behavior in vivo (4) and would require even more cautious validation.…”
Section: Topics Labeling: First Do No Harmmentioning
confidence: 99%
“…Figure 1 schematically illustrates an antibody labeled with lysine-linked moieties that facilitate detection by PET (Zr-89 chelated in desferrioxamine) and near-infrared fluorescence (IRDye800CW). This reagent was used in elegant dual-modality studies of antibody imaging reagents by Cohen et al (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IRDye800CW can be stably coupled to targeting molecules, such as peptides and monoclonal antibodies (mAbs), and can be detected with an NIR imaging camera (7,8).…”
mentioning
confidence: 99%